Amor Promiscuo: VIH y Visibilidad en el Chile de la Transición. - DE LA FUENTE, ALEJANDRO (Nomadías)
The following is a historical journey through the cities of Santiago and Concepción in Chile between 1987 and 1992, a period that we will call of "transition". We will present moments in which certain processes of HIV-AIDS visibility in the public sphere were combined with aesthetic tools from the visual arts' field such as graphics, performance and video-photography. We will focus mainly on the artistic collective Mares of the Apocalypse and on civil society organizations such as the Chilean Corporation for the Prevention of AIDS, the Center for Education and Social Health Prevention, among others. In reviewing this series of visibility strategies, we will describe the cultural and official scenario of sexual and health policies regarding HIV-AIDS and generate a dialogue or tension between both scenarios.